2014
DOI: 10.1016/j.elecom.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical sensing with nanopores: A mini review

Abstract: 13We discuss representative electrochemical nanopore sensing strategies, highlighting their 14 underlying theoretical principles, and limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 38 publications
0
51
0
Order By: Relevance
“…In electrochemical analysis, enhanced catalytic effect of nanoporous structures comes from its geometrical features, such as irregularity, large roughness and high porosity. Significant electrical signal amplification is supported by the nano-confinement effect, which allows increased probability for charge transfer between molecules and electrode surface [32,33]. It was reported that nanoporous gold coupled with several enzymes were able to show good sensing performance in detections of ethanol (with alcohol dehydrogenase (ADH)), hydrogen peroxide (with artificial peroxidase) and glucose (with glucose oxidase) [34].…”
Section: Introductionmentioning
confidence: 99%
“…In electrochemical analysis, enhanced catalytic effect of nanoporous structures comes from its geometrical features, such as irregularity, large roughness and high porosity. Significant electrical signal amplification is supported by the nano-confinement effect, which allows increased probability for charge transfer between molecules and electrode surface [32,33]. It was reported that nanoporous gold coupled with several enzymes were able to show good sensing performance in detections of ethanol (with alcohol dehydrogenase (ADH)), hydrogen peroxide (with artificial peroxidase) and glucose (with glucose oxidase) [34].…”
Section: Introductionmentioning
confidence: 99%
“…Several excellent reviews have summarized the recent progress on single-entity analysis by using electrochemical techniques, [14][15][16][17][18][19][20][21][22][23] mainly focusing on strategies and methodologies for single-entity analysis, especially for hard particles. First, electrochemical experiments are conducted in solution, even in solutions with high salt concentrations, which can largely maintain the structures and properties of vesicles as in biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…With the ability to characterize a single particle, nanofluidic RPS is a strong candidate for resolving the technological gap of conventional nanoparticle analyses, e.g., nanoparticle‐tracking analysis and dynamic light scattering . Currently, two major obstacles in this technology are the extremely low particle‐to‐pore volume ratio (<0.01%) and short nanoparticle translocation time (10–1000 µs) . The magnitude of resistive pulses is proportional to the particle‐to‐pore volume ratio; therefore, an extremely small volume of nanoparticles causes the generation of a minute pulse that is difficult to detect .…”
Section: Introductionmentioning
confidence: 99%